Trends and factors determining the place of delivery in a rural setting of Maharashtra - Kushwaha, Arvind Singh; Kushwaha, Anshika Singh (International Journal Of Community Medicine And Public Health, 2018)
Background: The MMR in India was 212 according to SRS 2009, which translates to about 55,000 women dying annually due to pregnancy and related causes. Very few studies have been done to understand thebirthing practices in the rural setup. This study was conducted to estimate the trends of delivery and elucidate the various socio-cultural factors determining the birthing practices in rural India. Methods: A cross sectional study was conducted among married women, aged 18 to 49 years residing in a Gram Panchayat Kasurdi of Daund Taluka in Pune district from March to October 2016. A structured, interview based, pre-tested questionnaire was used for collection of the data. Results: Most of the study subjects were literate (69.5%), housewife (46.2%) and residing in joint family (39.7%). Four fifth (83%) of the women had at least two children. Despite this, it was both the partners (47.8%) who were the most common decision maker for the place of delivery. Though most (81.6%) of women wanted to deliver in an institution but home delivery was found in one fourth cases (26.5%). The most common reason for home delivery was ease, comfort and privacy while the most common reason for institutional delivery was that it was safe. Conclusions: There is a wide gap between where the rural women want to deliver and where they actually do. As the parity rises complacency is seen in utilization of the ANC services and institutional delivery.